A heat-resistant high-strength aluminum alloy material for additive manufacturing and a preparation method thereof
By using specific heat-resistant high-strength aluminum alloy materials in additive manufacturing to form a three-dimensional network precipitation phase, the problem of degradation of mechanical properties of existing aluminum alloy materials under high temperature conditions is solved, and the field of aerospace has been realized. Efficient application.
Patent Information
- Application Number
- CN202411676555.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The mechanical properties of existing aluminum alloy materials in additive manufacturing are degraded and it is difficult to meet the application needs under high temperature conditions, especially in the fields of aerospace and aerospace.
Using specific compositions of heat-resistant high-strength aluminum alloy materials, including Mg, Mn, Cu, Ca, Be and Y elements, it is prepared by aerosol spraying, screening and additive manufacturing processes to form a three-dimensional network precipitation phase to improve mechanics Performance and heat resistance.
It showed good mechanical properties at room temperature and high temperature conditions, including tensile strength and yield strength, and maintained at 400°C for more than 500 hours, significantly improving the high-temperature service life of the material.
Smart Images

Figure CN119162494B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat-resistant high-strength aluminum alloy material for additive manufacturing and a preparation method thereof, belonging to the technical field of aluminum alloy materials. Background Art
[0002] Additive manufacturing has good designability and can meet the needs of rapid prototyping of complex parts, and has broad application prospects in the fields of aviation, aerospace, electronics, etc. As an excellent lightweight structural material, aluminum alloy has been widely used in military and civilian fields, and has also become a hot material for the development and application of additive manufacturing technology.
[0003] Due to fluidity limitations, early research and application focused on cast aluminum-silicon alloy materials with good fluidity. Among them, the commonly used aluminum alloy material for additive manufacturing is AlSi10Mg, which has a room temperature tensile strength of 300MPa and a high temperature tensile strength of about 100MPa at 200°C. Its mechanical properties are only equivalent to those of the cast ZL104 alloy, making it difficult to give full play to the technical advantages of additive manufacturing. Other traditional high-strength aluminum alloy materials such as 2XXX and 7XXX series have poor additive manufacturing process performance, that is, there are a large number of thermal cracks in the structure of the parts obtained after additive manufacturing, which is difficult to meet the technical requirements of additive manufacturing technology. Although the problem of cracking in additive manufacturing can be solved to a certain extent by adding a large amount of elements such as Sc and Zr, this greatly increases the manufacturing cost and does not significantly improve its high temperature resistance.
[0004] As the thrust requirements of my country's aero-engines gradually increase, higher requirements are also placed on the service temperature of cold-end components. Traditional heat-resistant aluminum alloys, such as 2XXX series alloys and Al-Fe series alloys, have a heat-resistant temperature that is difficult to exceed 300°C. Therefore, it is necessary to develop a heat-resistant and high-strength aluminum alloy material for additive manufacturing for application scenarios that can withstand higher temperatures, in order to promote the further development and application of additive manufacturing aluminum alloys. Summary of the invention
[0005] In order to improve the defects of the aluminum alloy materials in the prior art that cannot meet the requirements of additive manufacturing technology and the mechanical properties of the aluminum alloy materials are significantly reduced under high temperature conditions, the present invention provides a heat-resistant high-strength aluminum alloy material for additive manufacturing and a preparation method thereof. The heat-resistant high-strength aluminum alloy material has heat-resistant characteristics, and has good mechanical properties (such as tensile strength and yield strength) and ductility at room temperature and high temperature conditions (such as 400°C), and has a long service life (≥500 hours) under high temperature conditions (such as 400°C).
[0006] The object of the present invention is achieved through the following technical solutions:
[0007] A heat-resistant high-strength aluminum alloy material, wherein the heat-resistant high-strength aluminum alloy material comprises the following components in mass percentage: Mg: 4.5-5.5%, Mn: 1.3-1.9%, Cu: 2.0-3.0%, Ca: 1.2-2.0%, Be: 0.05-0.10%, Y: 0.03-0.09%, impurity elements are less than or equal to 0.2%, and the balance is aluminum;
[0008] The mass ratio of the sum of the masses of the Mg element and the Cu element to the mass ratio of the Ca element is (Mg+Cu) / Ca≤5.1.
[0009] According to an embodiment of the present invention, (Mg+Cu) / Ca is 3.25-5.1, for example, 3.25, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0 or 5.1.
[0010] According to the embodiment of the present invention, it is found that when the heat-resistant high-strength aluminum alloy material includes the following components in mass percentage: Mg: 4.5-5.5%, Mn: 1.3-1.9%, Cu: 2.0-3.0%, Ca: 1.2-2.0%, Be: 0.05-0.10%, Y: 0.03-0.09%, impurity elements are less than or equal to 0.2%, and the balance is aluminum; and the mass ratio of the sum of the mass of the Mg element and the Cu element to the mass of the Ca element (Mg+Cu) / Ca≤5.1, the heat-resistant high-strength aluminum alloy material has heat-resistant characteristics, and has good mechanical properties (such as tensile strength and yield strength) and ductility at room temperature and high temperature conditions. When (Mg+Cu) / Ca>5.1, the precipitated phase in the alloy matrix begins to crack, which will significantly affect the mechanical properties and heat resistance of the alloy, and it is impossible to obtain an aluminum alloy material with good mechanical properties at both room temperature and high temperature conditions.
[0011] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, 5.1%, 5.2%, 5.3%, 5.4% or 5.5% Mg.
[0012] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, and 1.9% of Mn.
[0013] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0% Cu.
[0014] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0% Ca.
[0015] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.10% Be.
[0016] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material includes 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or 0.09% Y.
[0017] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material is used in the field of additive manufacturing.
[0018] According to an embodiment of the present invention, the heat-resistant and high-strength aluminum alloy material is prepared by an additive manufacturing process; preferably, the heat-resistant and high-strength aluminum alloy material is based on Al-Mg-Cu-Ca alloy, micro-alloying elements (Be element and Y element) are appropriately added, and is prepared by an additive manufacturing process.
[0019] According to the embodiment of the present invention, the present invention introduces Ca element as the main element into the alloy system. Ca element can react with other elements and form a continuous three-dimensional mesh Al-Mg-Cu-Ca phase in the matrix. These continuous mesh intermetallic compounds are distributed at the grain boundaries and are very stable when heated, which can significantly improve the high temperature performance of aluminum alloy materials; further combined with the rapid cooling process in the additive manufacturing process, the formed three-dimensional mesh Al-Mg-Cu-Ca phase is made finer. In addition, the precipitation of the three-dimensional mesh Al-Mg-Cu-Ca phase can effectively pin at the grain boundaries, thereby improving the mechanical properties of the alloy; on the other hand, it can also effectively inhibit the migration, growth and merging of grain boundaries, thereby improving the mechanical properties of the alloy under high temperature conditions.
[0020] According to an embodiment of the present invention, the Y element and the Be element introduced into the alloy system of the present invention are trace elements. The introduction of the Y element and the Be element can effectively reduce the formation of oxide film on the surface of the alloy powder. Further combined with the high-purity argon environment in the additive manufacturing process, the deep oxidation of the surface of the alloy powder can be effectively inhibited, and the generation of oxide inclusions, holes and bubbles in the additive manufacturing process can be reduced.
[0021] According to the embodiment of the present invention, a large amount of Mn element is also introduced into the alloy system. The introduction of Mn element can promote the precipitation of a large amount of Al at the grain boundary. 6 Mn phase, and Al6 The Mn phase is precipitated together with the Al-Mg-Cu-Ca phase, which can further enhance the grain boundary strengthening and pinning effect of the three-dimensional network precipitation phase (Al-Mg-Cu-Ca phase), and is more conducive to the improvement of the room temperature and high temperature properties of the alloy; further combined with the rapid cooling process in the additive manufacturing process, a certain amount of Mn element can also be dissolved into the alloy matrix, which is beneficial to the improvement of the mechanical properties of the alloy.
[0022] The present invention also provides a method for preparing the above-mentioned heat-resistant high-strength aluminum alloy material, the method comprising the following steps:
[0023] (1) Using aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-manganese master alloy ingots, aluminum-calcium master alloy ingots, aluminum-yttrium master alloy ingots and aluminum-beryllium master alloy ingots as raw materials, smelting them in a vacuum atomization furnace under the protection of inert gas to obtain alloy liquid; then crushing the alloy liquid by inert gas to obtain alloy powder;
[0024] (2) Screening the alloy powder obtained in step (1) to obtain an alloy powder having a particle size ranging from 6.5 to 38 μm; then placing the alloy powder in an explosion-proof drying oven for drying;
[0025] (3) performing additive manufacturing on the alloy powder of step (2), wherein the additive manufacturing comprises first performing powder spreading on the alloy powder of step (2) more than twice using a laser powder bed melting device; and then performing molding on the alloy powder of step (2) using a laser powder bed melting device to obtain an alloy product;
[0026] (4) Heat treating the alloy product obtained in step (3).
[0027] According to an embodiment of the present invention, in step (1), the purity of the aluminum ingot, magnesium ingot, aluminum-copper master alloy ingot, aluminum-manganese master alloy ingot, aluminum-calcium master alloy ingot, aluminum-yttrium master alloy ingot and aluminum-beryllium master alloy ingot is not particularly defined, and can be any purity conventionally used in the art for preparing aluminum alloy materials.
[0028] According to an embodiment of the present invention, in step (1), the feed ratio of the aluminum ingot, magnesium ingot, aluminum-copper master alloy ingot, aluminum-manganese master alloy ingot, aluminum-calcium master alloy ingot, aluminum-yttrium master alloy ingot and aluminum-beryllium master alloy ingot meets the mass percentage of the heat-resistant and high-strength aluminum alloy material defined above.
[0029] According to an embodiment of the present invention, in step (1), the vacuum atomization furnace is a commonly used device in the art that can melt the above raw materials.
[0030] According to an embodiment of the present invention, in step (1), the smelting temperature is 900-1000°C.
[0031] According to an embodiment of the present invention, in step (1), the inert gas is argon; preferably argon with a purity of ≥99.99%.
[0032] According to an embodiment of the present invention, in step (1), the crushing has no special definition, and the introduced inert gas can disperse the alloy liquid to achieve the preparation of alloy powder.
[0033] According to an embodiment of the present invention, in step (1), alloy powder can be obtained by crushing the alloy liquid by inert gas, and the alloy powder falls into a receiving device at the bottom of the vacuum atomization furnace under an inert atmosphere, thereby achieving cooling treatment of the alloy powder.
[0034] According to an embodiment of the present invention, in step (2), the sieving is performed by selecting a conventional sieving method in the art, as long as the alloy powder with a particle size range of 6.5 to 38 μm can be obtained. The sieving is, for example, selecting a sieve with different meshes (such as 400 mesh, 500 mesh, 600 mesh, 625 mesh, 700 mesh, 800 mesh, 1000 mesh, 1340 mesh, 1800 mesh or 2000 mesh) to sieve the alloy powder of step (1); illustratively, selecting a sieve with 400 mesh and 1800 mesh can obtain an alloy powder with a particle size range of 8 to 38 μm; selecting a sieve with 625 mesh and 2000 mesh can obtain an alloy powder with a particle size range of 6.5 to 20 μm.
[0035] According to an embodiment of the present invention, in step (2), the drying temperature is 80° C.-120° C.; and the drying time is 2-5 hours.
[0036] According to an embodiment of the present invention, in step (2), the drying is, for example, first placing the alloy powder in a tray and spreading it flat, with a thickness of ≤20 mm, then placing the alloy powder and the tray into an explosion-proof drying oven, and finally drying at a temperature of 80°C-120°C for 2-5 hours. After drying, the alloy powder is cooled to room temperature in the furnace.
[0037] According to an embodiment of the present invention, in step (3), the alloy powder of step (2) is spread 2-10 times using a laser powder bed melting device, that is, the number of times of spreading the powder is 2-10 times.
[0038] Preferably, the alloy powder of step (2) is spread 2-5 times using a laser powder bed melting device, that is, the number of times of spreading the powder is 2-5 times, for example, 2 times, 3 times, 4 times or 5 times.
[0039] The study found that when the laser powder bed melting equipment is used to spread the alloy powder more than twice, the friction between the scraper and the alloy powder during the spreading process will generate static electricity, which can adsorb tiny powders (such as particles with a diameter less than 5μm) and satellite particles on the powder (satellite particles refer to particles adsorbed on the surface of large particles and with a size less than 1μm), which is beneficial to the improvement of the fluidity of the alloy powder; at the same time, when the laser powder bed melting equipment is used to spread the alloy powder more than twice, the scraper will apply a certain pressure to the already formed powder layer during the repeated spreading process, which is beneficial to the densification of the powder layer. Combining the above two aspects, the internal quality of the alloy products after the alloy powder is formed can be significantly improved.
[0040] According to an embodiment of the present invention, exemplarily, multiple powder spreading operations can be achieved by reducing the thickness of a single powder spreading. For example, before laser forming, the thickness of a single powder spreading is set to 10 μm. After three powder spreading operations, a powder layer with a total thickness of 30 μm can be obtained.
[0041] According to an embodiment of the present invention, in step (3), the total thickness of the powdering layer obtained after powdering is 20-40 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0042] According to an embodiment of the present invention, in step (3), the thickness of a single powder spreading is 5-20 μm, for example, 5 μm, 10 μm, 15 μm or 20 μm.
[0043] According to an embodiment of the present invention, in step (3), the molding is carried out in an argon atmosphere, and the oxygen content of the argon atmosphere is ≤80ppm; illustratively, the oxygen content of the argon atmosphere is ≤70ppm, ≤60ppm, ≤50ppm, ≤40ppm, ≤30ppm, ≤20ppm, ≤10ppm. Studies have found that by controlling the oxygen content during the molding process (i.e., the printing environment), the deep oxidation of the alloy powder surface can be effectively suppressed, and the generation of oxidized inclusions, pores, and bubbles during the additive manufacturing process can be reduced.
[0044] According to an embodiment of the present invention, in step (3), the forming conditions are as follows: the laser power is 160-290 W, the scanning rate is 1000-2200 mm / s, and the overlap spacing is 0.1-0.2 mm.
[0045] According to an embodiment of the present invention, in step (3), the temperature of preheating the substrate during the forming process is 50-250°C, for example, 50°C, 60°C, 80°C, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C or 250°C.
[0046] According to an embodiment of the present invention, in step (3), the number of repeated scans during the molding process is 0 or 1; wherein, the number of repeated scans being 0 means only 1 scan is performed, and the number of repeated scans being 1 means 2 scans are performed.
[0047] According to an embodiment of the present invention, in step (4), the temperature of the heat treatment is 300-350°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C; the time of the heat treatment is 1.5-3 hours, for example, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0048] According to an embodiment of the present invention, in step (4), the heat treatment is performed in an air atmosphere.
[0049] The present invention also provides a heat-resistant high-strength aluminum alloy material, which is prepared by the above method.
[0050] According to an embodiment of the present invention, the room temperature tensile strength of the heat-resistant high-strength aluminum alloy material is greater than 560 MPa (for example, 560-590 MPa); the yield strength of the heat-resistant high-strength aluminum alloy material is greater than 500 MPa (for example, 500-530 MPa).
[0051] According to an embodiment of the present invention, the high-temperature tensile strength of the heat-resistant high-strength aluminum alloy material is above 400 MPa; the high-temperature yield strength of the heat-resistant high-strength aluminum alloy material is above 310 MPa; the high-temperature tensile strength and high-temperature yield strength are test results after the aluminum alloy material is kept at 400°C for 500 hours.
[0052] Compared with the existing AlSi10Mg alloy used for additive manufacturing, the alloy material of the present invention has higher mechanical properties. The room temperature tensile performance test shows that the tensile strength of the annealed heat-resistant high-strength aluminum alloy material reaches more than 560MPa, and the yield strength reaches more than 500MPa; after being kept at 400℃ for 500 hours, the tensile strength of the material is more than 400MPa, and the yield strength is more than 310MPa; this shows that the heat-resistant high-strength aluminum alloy material of the present invention has good room temperature mechanical properties and high temperature mechanical properties, which is helpful to realize the additive manufacturing of heat-resistant, high-strength, and lightweight structures in the fields of aviation, aerospace, shipbuilding, transportation, etc., and is conducive to the innovative development of additive manufacturing technology.
[0053] The preparation method of the aluminum alloy material of the present invention is simple. By screening alloy powders in a specific particle size range and selecting more than two powder spreading operations, a heat-resistant and high-strength aluminum alloy material whose internal quality meets the Class I requirements specified in GB / T 9438 (detected by X-ray) can be prepared.
[0054] Beneficial effects of the present invention:
[0055] The present invention provides a heat-resistant high-strength aluminum alloy material for additive manufacturing and a preparation method thereof. The heat-resistant high-strength aluminum alloy material is prepared by atomization spraying, screening and additive manufacturing processes using Al-Mg-Cu-Ca alloy as a matrix, appropriately adding micro-alloying elements. The heat-resistant high-strength aluminum alloy material is suitable for the field of additive manufacturing. The tensile strength of the annealed heat-resistant high-strength aluminum alloy material can reach more than 560MPa, and the yield strength exceeds 500MPa; the high-temperature tensile strength after being kept at 400°C for 500 hours can be maintained at more than 400MPa, and the yield strength can be maintained at more than 310MPa. Compared with the currently reported additively manufactured AlSi10Mg alloy, the room temperature strength and high-temperature strength of the heat-resistant high-strength aluminum alloy material of the present invention are significantly higher, reaching the level of traditional ultra-high-strength deformed aluminum alloys, and can meet the needs of aviation, aerospace, shipbuilding, transportation and other fields for additively manufactured heat-resistant high-strength aluminum alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 is a microstructure diagram of the aluminum alloy material of Example 1, wherein Figure 1 Figure a shows the metallographic structure of the annealed alloy; Figure 1 Figure b shows the TEM structure of the annealed alloy.
[0057] Figure 2 This is the microstructure diagram of the aluminum alloy material of Comparative Example 1.
[0058] Figure 3 is a powder microstructure diagram of the aluminum alloy material of Example 1 and Comparative Example 2, wherein Figure 3 Figure a in the figure is the original powder microstructure of the aluminum alloy material of Comparative Example 2; Figure 3 Figure b is a microstructure diagram of the aluminum alloy powder of Comparative Example 2 after powder spreading; Figure 3 Figure c is the microstructure of the powder of the aluminum alloy material of Example 1 after powder spreading.
[0059] Figure 4 This is the microstructure diagram of the aluminum alloy material of Comparative Example 4. DETAILED DESCRIPTION
[0060] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0061] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0062] Embodiment 1:
[0063] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Mn, Cu, Ca, Be, and Y, comprising the following components in percentage by mass: Mg: 4.8%, Mn: 1.6%, Cu: 1.7%, Ca: 1.4%, Be: 0.05%, Y: 0.04%, impurity elements are less than or equal to 0.15%, and the balance is aluminum.
[0064] (Mg+Cu) / Ca is 4.6.
[0065] The preparation process is as follows:
[0066] ① After weighing aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-manganese master alloy ingots, aluminum-calcium master alloy ingots, aluminum-yttrium master alloy ingots and aluminum-beryllium master alloy ingots in proportion, melt them in a crucible, crush the alloy liquid with argon gas to prepare alloy powder, and cool the alloy powder in an argon atmosphere.
[0067] ② Use 400 mesh and 1800 mesh sieves to sieve the alloy powder to obtain alloy fine powder with a particle size of 8~38μm.
[0068] ③Put the alloy fine powder on a tray and spread it flat with a thickness of 15 mm. Put it into an explosion-proof drying oven and dry it at 120°C for 2.5 hours, and cool it with the furnace.
[0069] ④ Use laser powder bed melting equipment to spread powder twice, and then form it. Use strip scanning strategy, laser power 265W, scanning rate 1600mm / s, total thickness of powder layer 35μm (thickness of the first powder is 15μm, thickness of the second powder is 20μm), overlap spacing 0.12mm. Argon is used for protection during the forming process, and the oxygen content in the argon atmosphere is controlled to be ≤50ppm. The substrate preheating temperature during the forming process is 100℃. Repeat the scan number 0 times. Take it out after cooling.
[0070] ⑤ Heat-treat the sample in a heating furnace at a holding temperature of 310°C for 2 hours, cool it with the furnace, and obtain an annealed heat-resistant high-strength additive aluminum alloy product to test its mechanical properties. Keep the product at 400°C for 500 hours to test its mechanical properties.
[0071] Embodiment 2:
[0072] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Mn, Cu, Ca, Be, and Y, comprising the following components in percentage by mass: Mg: 5.3%, Mn: 1.4%, Cu: 2.8%, Ca: 1.8%, Be: 0.08%, Y: 0.05%, impurity elements are less than or equal to 0.15%, and the balance is aluminum.
[0073] (Mg+Cu) / Ca is 4.5.
[0074] The preparation process is as follows:
[0075] ① After weighing aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-manganese master alloy ingots, aluminum-calcium master alloy ingots, aluminum-yttrium master alloy ingots and aluminum-beryllium master alloy ingots in proportion, melt them in a crucible, crush the alloy liquid with argon gas to prepare alloy powder, and cool the alloy powder in an argon atmosphere.
[0076] ② Use 625 mesh and 2000 mesh sieves to sieve the alloy powder to obtain alloy fine powder with a particle size of 6.5~20μm.
[0077] ③Put the alloy fine powder on a tray and spread it flat with a thickness of 20 mm, and put it into an explosion-proof drying oven and dry it at 100°C for 4 hours, and cool it with the furnace.
[0078] ④ Use laser powder bed melting equipment to spread powder 3 times, and then form it. Use strip scanning strategy, laser power 235W, scanning rate 1600mm / s, total thickness of powder layer 40μm (the thickness of the first powder is 10μm, the thickness of the second powder is 15μm, and the thickness of the third powder is 15μm), overlap spacing 0.12mm. Use argon gas for protection during the forming process, and control the oxygen content in the argon gas atmosphere ≤80ppm. The substrate preheating temperature during the forming process is 150℃. Repeat the scan number 0 times. Take it out after cooling.
[0079] ⑤ Heat-treat the sample in a heating furnace at a holding temperature of 320°C for 2 hours, cool it with the furnace, and obtain a heat-resistant and high-strength additive aluminum alloy product to test its mechanical properties. Keep the product at 400°C for 500 hours to test its mechanical properties.
[0080] Comparative Example 1: (Increasing the ratio of (Mg+Cu) / Ca)
[0081] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Mn, Cu, Ca, Be, and Y, comprising the following components in percentage by mass: Mg: 4.9%, Mn: 1.5%, Cu: 2.4%, Ca: 1.3%, Be: 0.08%, Y: 0.05%, impurities are less than or equal to 0.15%, and the balance is aluminum.
[0082] (Mg+Cu) / Ca is 5.61.
[0083] The preparation process is the same as that of Example 2.
[0084] Comparative Example 2: (no repeated application of powder, i.e., one application of powder)
[0085] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Mn, Cu, Ca, Be, and Y, comprising the following components in percentage by mass: Mg: 4.8%, Mn: 1.6%, Cu: 1.7%, Ca: 1.4%, Be: 0.05%, Y: 0.04%, impurities are less than or equal to 0.15%, and the balance is aluminum.
[0086] The preparation process is as follows:
[0087] Same as Example 1, except that:
[0088] ④ Use laser powder bed melting equipment to spread powder once, and then form it. Use strip scanning strategy, laser power 265W, scanning rate 1600mm / s, total thickness of powder layer 35μm (thickness of powder once is 35μm), overlap spacing 0.12mm. Argon is used for protection during the forming process, and the oxygen content of the atmosphere is controlled to 50ppm. The substrate preheating temperature during the forming process is 100℃. Repeat the scanning number 0 times. Take it out after cooling.
[0089] Comparative Example 3: (without Mn element)
[0090] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Cu, Ca, Be, and Y, comprising the following components in percentage by mass: Mg: 5.3%, Cu: 2.8%, Ca: 1.8%, Be: 0.08%, Y: 0.05%, impurities are less than or equal to 0.15%, and the balance is aluminum.
[0091] (Mg+Cu) / Ca is 4.5.
[0092] The preparation process is the same as in Example 2, except that:
[0093] ① After weighing aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-calcium master alloy ingots, aluminum-yttrium master alloy ingots and aluminum-beryllium master alloy ingots in proportion, melt them in a crucible, crush the alloy liquid with argon gas to prepare alloy powder, and cool the alloy powder in an argon atmosphere.
[0094] Comparative Example 4: (excluding Be and Y elements)
[0095] A heat-resistant high-strength aluminum alloy for additive manufacturing containing Mg, Mn, Cu and Ca, comprising the following components in percentage by mass: Mg: 5.3%, Mn: 1.4%, Cu: 2.8%, Ca: 1.8%, impurities are less than or equal to 0.15%, and the balance is aluminum.
[0096] (Mg+Cu) / Ca is 4.5.
[0097] The preparation process is the same as in Example 2, except that:
[0098] ① After weighing aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-manganese master alloy ingots, and aluminum-calcium master alloy ingots in proportion, place them in a crucible for melting, use argon gas to crush the alloy liquid to prepare alloy powder, and cool the alloy powder in an argon atmosphere.
[0099] Figure 1 is a microstructure diagram of the aluminum alloy material of Example 1, wherein Figure 1 Figure a shows the metallographic structure of the annealed alloy. Figure 1 Figure a shows that the annealed alloy has a dense structure; Figure 1 Figure b shows the TEM structure of the annealed alloy. Figure 1 In Figure b, we can see that the three-dimensional network precipitation phase Al-Mg-Cu-Ca phase and Al 6 Mn is generated concomitantly.
[0100] Figure 2 This is a microstructure diagram of the aluminum alloy material of Example 1. It can be seen from the diagram that cracks have appeared in the network precipitation phase.
[0101] Figure 3 is a powder microstructure diagram of the aluminum alloy material of Example 1 and Comparative Example 2, wherein Figure 3 Figure a in the figure is the original powder microstructure of the aluminum alloy material of Comparative Example 2; Figure 3 Figure b is a microstructure diagram of the aluminum alloy powder of Comparative Example 2 after powder spreading; Figure 3 Figure c is a microstructure diagram of the aluminum alloy powder of Example 1 after powder spreading. Figure 3 Figures a and b show that there are many satellite balls in the alloy powder; Figure 3 It can be seen from Figure c that the number of satellite balls in the alloy powder is significantly reduced; this means that when the laser powder bed melting equipment is used to spread the alloy powder more than twice, the friction between the scraper and the alloy powder during the spreading process will generate static electricity, which can absorb tiny powders (such as particles less than 5μm in size) and satellite ball particles on the powder (satellite ball particles refer to particles less than 1μm in size that are adsorbed on the surface of large powder particles).
[0102] Figure 4This is the microstructure of the aluminum alloy material of Example 4. It can be seen from the figure that there are obvious tiny holes in the matrix.
[0103] The room temperature and high temperature mechanical properties of the additively manufactured aluminum alloy products of the embodiments and comparative examples were tested. GB / T 228.1 “Tensile test of metallic materials Part 1: Room temperature test method” and GB / T 4338 “High temperature tensile test method of metallic materials” were used to test the mechanical properties of the cut test bars at the same position of the additively manufactured aluminum alloy products at room temperature and 400°C. The test results are shown in Table 1.
[0104] Table 1 Performance test results of heat-resistant high-strength aluminum alloy materials of the embodiments and comparative examples
[0105]
[0106] From the comparison of the data in Table 1, it can be seen that the aluminum alloys prepared by using the alloy composition and forming process of the present invention all exhibit optimal room temperature and high temperature mechanical properties (as shown in Example 1 and Example 2).
[0107] When (Mg+Cu) / Ca>5.1 (such as Comparative Example 1), cracks begin to appear in the precipitated phase of the alloy obtained by additive manufacturing (such as Figure 2 As shown in Example 2, such an alloy fails preferentially from the precipitation phase cracks when subjected to external loads, so its tensile strength, yield strength and elongation are significantly lower than those of Example 2.
[0108] When the element composition of the alloy is adjusted, such as reducing the addition of Y and Be in Comparative Example 4, the surface of the alloy powder is more easily oxidized, which makes the fluidity of the alloy powder worse, resulting in obvious small holes in the alloy after molding (such as Figure 4 As shown); in Comparative Example 3, the addition of Mn element is reduced, which weakens the strengthening effect of the intergranular network precipitation phase to a certain extent, so that the tensile strength, yield strength and elongation of the alloy also show different degrees of decline.
[0109] In comparative example 2, the alloy powder was laser formed after only one powder spreading during the additive manufacturing process. Since there is a certain amount of satellite ball powder in the original alloy powder, although the rear star powder is reduced to a certain extent after one powder spreading (such as Figure 3 However, it will still affect the packing density and flow properties of the alloy powder in the subsequent molding process, resulting in a decrease in the density of the additively manufactured aluminum alloy products, which in turn leads to a significant decrease in the tensile strength, yield strength and elongation.
[0110] In summary, the present invention is based on the design of a three-dimensional heat-resistant network intergranular precipitation phase. On this basis, combined with the rapid solidification advantage of additive manufacturing, an aluminum alloy material for additive manufacturing that is resistant to high temperatures of 400°C can be prepared, and the obtained aluminum alloy material has a service life of ≥500 hours under high temperature conditions, which greatly improves its service life under high temperature conditions.
[0111] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A heat-resistant high-strength aluminum alloy material, wherein: The heat-resistant high-strength aluminum alloy material comprises the following components in percentage by mass: Mg: 4.5-5.5%, Mn: 1.3-1.9%, Cu: 2.0-3.0%, Ca: 1.2-2.0%, Be: 0.05-0.10%, Y: 0.03-0.09%, impurity elements are less than or equal to 0.2%, and the balance is aluminum; The mass ratio of the sum of the masses of the Mg element and the Cu element to the mass ratio of the Ca element is (Mg+Cu) / Ca≤5.
1.
2. The heat-resistant high-strength aluminum alloy material according to claim 1, wherein: (Mg+Cu) / Ca is 3.25-5.
1.
3. The heat-resistant high-strength aluminum alloy material according to claim 1 or 2, wherein: The heat-resistant high-strength aluminum alloy material is prepared by an additive manufacturing process.
4. A method for preparing a heat-resistant high-strength aluminum alloy material according to any one of claims 1 to 3, the method comprising the following steps: (1) Using aluminum ingots, magnesium ingots, aluminum-copper master alloy ingots, aluminum-manganese master alloy ingots, aluminum-calcium master alloy ingots, aluminum-yttrium master alloy ingots and aluminum-beryllium master alloy ingots as raw materials, smelting them in a vacuum atomization furnace under the protection of inert gas to obtain alloy liquid; then crushing the alloy liquid by inert gas to obtain alloy powder; (2) Screening the alloy powder obtained in step (1) to obtain alloy powder with a particle size ranging from 6.5 to 38 μm; then placing the alloy powder in an explosion-proof drying oven for drying; (3) performing additive manufacturing on the alloy powder of step (2), wherein the additive manufacturing comprises first performing powder spreading on the alloy powder of step (2) more than twice using a laser powder bed melting device; and then performing molding on the alloy powder of step (2) using a laser powder bed melting device to obtain an alloy product; (4) Heat treating the alloy product obtained in step (3).
5. The preparation method according to claim 4, wherein In step (1), the smelting temperature is 900-1000° C.; and / or, in step (2), the drying temperature is 80° C.-120° C.; and the drying time is 2-5 hours.
6. The preparation method according to claim 4, wherein In step (3), the alloy powder of step (2) is spread 2-10 times by using a laser powder bed melting device, that is, the number of times of spreading the powder is 2-10 times; And / or, in step (3), the total thickness of the powder layer obtained after powdering is 20-40 μm; And / or, in step (3), the thickness of a single powder coating is 5-20 μm.
7. The preparation method according to claim 4, wherein In step (3), the molding is carried out in an argon atmosphere, and the oxygen content of the argon atmosphere is ≤80ppm; and / or, in step (3), the molding conditions meet: laser power is 160-290W, scanning rate is 1000-2200mm / s, overlap spacing is 0.1-0.2mm; and / or, in step (3), the substrate preheating temperature during the molding process is 50-250°C.
8. The preparation method according to claim 4, wherein In step (4), the heat treatment temperature is 300-350° C. and the heat treatment time is 1.5-3 hours.
9. A heat-resistant high-strength aluminum alloy material, which is prepared by the method described in any one of claims 4 to 8.
10. The heat-resistant high-strength aluminum alloy material according to any one of claims 1 to 2 and 9, wherein: The room temperature tensile strength of the heat-resistant high-strength aluminum alloy material is above 560MPa; the yield strength of the heat-resistant high-strength aluminum alloy material is above 500MPa; the high-temperature tensile strength of the heat-resistant high-strength aluminum alloy material is above 400MPa; the high-temperature yield strength of the heat-resistant high-strength aluminum alloy material is above 310MPa; the high-temperature tensile strength and high-temperature yield strength are the test results after the alloy is kept at 400°C for 500 hours.
Citation Information
Patent Citations
Additively manufactured high-temperature aluminum alloys, and feedstocks for making the same
CN113227421A
High-strength heat-resistant damage-resistant aluminum alloy powder as well as preparation method and application thereof
CN115874088A